The role of social innovation in tackling global poverty and vulnerability - Millard, Jeremy; Fucci, Vincenzo (Frontiers in Sociology, 2023)
Tackling the rapid rise in global poverty is one of the most pressing challenges the world faces today, especially in this new age of turbulence. On top of the ongoing environmental crisis, the last fifteen years has been rocked by the financial crisis of 2007–8, compounded by the 2020 Covid-pandemic and then by the 2022 war in Ukraine, each of which has negatively impacted all aspects of sustainable development. Although in practice many development organizations have been using the methods and processes of social innovation to tackle poverty and vulnerability for many years, it is only recently that they have specifically begun to analyse and codify its contribution to these and other SDGs. Social innovation provides beneficial social outcomes for citizens and other actors, often at local level with the strong bottom-up involvement of civil society and through its cross-actor, cross-sector, cross-disciplinary and cross-cutting strengths. Importantly, it aims to empower those with a social need, particularly when they have little to begin with. It focuses on increasing the beneficiaries' own agency and capability rather than passively only relying on others to act on their behalf. This is done by transforming social relationships and developing new collaborative processes. Amongst a wide range of recent and contemporary sources, this paper analyses a large scale quantitative and qualitative global survey of social innovations that tackle poverty and vulnerability in different global regions. It examines various definitions of poverty, including extreme, absolute and relative measures as well as arguably more useful approaches like the Multidimensional Poverty Index. It proposes how social innovation should be recalibrated to meet the increasing threats of the new age of turbulence, including by deploying the sociological lens of the agency-structure dichotomy to show why the public sector needs to become involved more proactively in social innovation. It also looks at certain myths around poverty and vulnerability, examines why we need to revise our understanding of sustainable development and resilience, and why a new nexus approach is needed that combines SDG1 with other strongly related SDGs.